Do combined glucosamine sulfate and chondroitin sulfate supplements affect condylar remodelling during functional appliance therapy? - Barley Gosia; Shen Gang; Almuzian Mohammed; Jones Alan; Oliver Rema; Petocz Peter; Walsh William R.; Darendeliler M. Ali (Sciendo, 2018)
The purpose of this study was to qualitatively and quantitatively analyse the effect of glucosamine sulfate and chondroitin sulfate supplements on condylar remodelling in conjunction with bite-jumping functional appliance therapy in rats.